1898 Ga. Laws 107-08 - (:unkn) unknown (My University, 1898)
An Act to Make it Unlawful for any Person to Wilfully and Wantonly Fire Off or Discharge any Loaded Gun or Pistol on Sunday, Except in Defense of Person or Property, § 1: Prohibited wilfully or wantonly firing off or discharging any loaded gun or pistol on Sunday.
Keywords: DISCHARGE